High levels of circulating osteopontin in inflammatory lung disease regardless of Sars‐CoV‐2 infection - Cappellano, Giuseppe (EMBO Mol Med, 2021)
This study independently confirms increased levels of osteopontin in COVID‐19 patients but also suggests that osteopontin cannot be used as a biomarker of SARS‐CoV‐2 infection, as elevated levels of circulating osteopontin are found in inflammatory lung disease regardless of SARS‐CoV‐2 infection.[Image: see text]